Influence of the methods of selecting parent pairs on the variability of breeding characters of the Ayrshire cattle - Voitenko, S.; Petrenko, M.; Shaferivskyi, B. (Scientific Progress & Innovations, 2023)
The Ayrshire breed of cattle in Ukraine is involved in the process of milk production, but there is not enough information about it, especially regarding the realization of the genetic potential of animals depending on the method of selection of parent pairs, which makes it necessary to focus on the research of this problem. The paper presents the results of studies of the live weight of Ayrshire heifers, obtained by intrabreed and interbreed selection of parental pairs in the postnatal period, identified lines and crosses of lines that provide the offspring with a high growth rate, determined the most optimal age for selecting heifers and the relationship between live weight with the age of the first insemination, the influence of the selection of parental pairs on the manifestation of the genetic potential of milk, the content of fat and protein in the milk of cows of the first and third lactation is determined. The research was carried out at the State enterprise Experimental farm «Dekabrysty» Institute of pig breeding and agro-industrial production of the National Academy of Agrarian Sciences of Ukraine and the Institute of Animals Breeding and Genetics named after M. V. Zubets of National Academy of Agrarian Science of Ukraine according to the program of scientific research 31 "Genetic improvement of agricultural animals, their reproduction and preservation of biodiversity". Among the methods of intrabreeding of Ayrshire cattle, according to average group indicators, interlineal selection of parent pairs is recognized as the best, as it contributes to the higher realization of the genetic potential of animals in terms of live weight and average daily gains. The possibility of selecting heifers based on their live weight at the age of 15 months has been proven, and the relationship between the trait and production maturity has been established. Cows of the Ayrshire breed, regardless of origin and lineal affiliation, increased hope with increasing age in lactation with significant intragroup variability of the breeding trait. Cows obtained by intralineal selection of parent pairs had higher milk productivity compared to interlineal selection. The content of fat and protein in milk did not reliably differ from the origin of cows, milk yield, and age during lactation. Interbreeding proved to be the most effective method of increasing the growth rate of heifers and milk productivity of cows, compared to intraline and interline selection of parent pairs, but the first-generation crossbreeds from the crossing of the Ayrshire breed with the Red Norwegian significantly differ from purebred individuals in the type of body structure and color of animals, which is required to be taken into account in breeding work with the breed. The method of selection of parental pairs had a reliable influence on the live weight of animals at the age of 3, 12 and 15 months (4.19, 5.81 and 6.34 %) and the hope of cows of the first lactation (9.4 %), and not reliably on the content of fat and protein in milk (0.2 % and 0.6 %).